Erythrocyturia and proteinuria conversion in post-streptococcal acute glomerulonephritis - I Ketut Suarta (Indonesian Pediatric Society, 2006)
Background Acute glomerulonephritis (AGN) is a sudden onsetof macroscopic hematuria and edema. The chronic post-strepto-coccal acute glomerulonephritis (PSAGN) can be predicted if mi-croscopic hematuria, proteinuria, and low serum complement C3level are present for a period exceeding six months after initial onsetof illness. It is prudent to follow the course of PSAGN until proteinurianormalizes and microhematuria disappears in urinalysis.Objective To acquire the time of erythrocyturia and proteinuriaconversion in post-streptococcal acute glomerulonephritis (PSAGN)among children.Methods A retrospective cohort study on children with PSAGNwas conducted in the Pediatric Outpatient Clinic and Ward atSanglah Hospital, Denpasar, Bali from January 2001-December2003. All subjects were recorded for clinical and laboratory signs,including initial symptoms, history of previous streptococcal infec-tions, blood pressure, complete blood count, serum albumin, ASTOtiter, complement C3 level, BUN, and serum creatinin. Erythrocyt-uria and proteinuria follow-ups were done by recording urinalysisfindings for a six-month period after initial onset.Results Thirty subjects 21 boys and 9 girls, mean age 8.7 (SD 2.5)years] with PSAGN were enrolled in the study, 16 had hematuria withedema. Twenty-one subjects had the history of upper respiratory tractinfections and 9 with skin infections. Mean systolic blood pressure was141.3 (SD 21.8) mmHg, mean diastolic blood pressure was 90.8 (SD16.3) mmHg, mean ASTO titer was 1103.3 (SD 686.1) IU/ml, and meancomplement C3 level was 42.2 (SD 15.5) mg/dl. Urinalysis monitoringshowed 2/30, 9/30, 12/30, 22/30, 27/30 subjects had conversion he-maturia at the first, second, third, fourth, and fifth month, respectively.Median duration of erythrocyturia conversion was 4.0 months (95% CI:3.53-4.47). There were 11/30, 18/30, 21/30, 23/30, 25/30, 26/30 sub-jects with proteinuria conversion at the first, second, third, fourth, fifth,and sixth month, respectively. Median duration of proteinuria conver-sion was 2.0 months (95% CI: 1.25-2.75).Conclusion Three out of 30 children remained with persistenthematuria and 4 of 30 remained with persistent proteinuria